Reputation, Voluntary Mobility and Wages - Keith, Kristen (The Review of Economics and Statistics, 1993)
This study analyzes the effect of voluntary mobility on subsequent wages to discover if there are wage penalties associated with repeated mobility. To reduce the endogeneity between wages and voluntary mobility, the sample is restricted to young males on their first job following a permanent layoff. Using respondents from the National Longitudinal Survey of Youth, ordinary least squares wage equations from the layoff sample are compared to those from a sample of workers who remained employed. The evidence shows that voluntary mobility differentially affects the wage equations of the restricted and the unrestricted samples. Copyright 1993 by MIT Press.